Satisfaction with medication in coronary disease treatment: psychometrics of the Treatment Satisfaction Questionnaire for Medication - Ana Carolina Sauer Liberato; Roberta Cunha Matheus Rodrigues; Thaís Moreira São-João; Neusa Maria Costa Alexandre; Maria Cecília Bueno Jayme Gallani (Revista Latino-Americana de Enfermagem, 2016)
Abstract Objective: to psychometrically test the Brazilian version of the Treatment Satisfaction Questionnaire for Medication - TSQM (version 1.4), regarding ceiling and floor effect, practicability, acceptability, reliability and validity. Methods: participants with coronary heart disease (n=190) were recruited from an outpatient cardiology clinic at a university hospital in Southeastern Brazil and interviewed to evaluate their satisfaction with medication using the TSQM (version 1.4) and adherence using the Morisky Self-Reported Measure of Medication Adherence Scale and proportion of adherence. The Ceiling and Floor effect were analyzed considering the 15% worst and best possible TSQM scores; Practicability was assessed by time spent during TSQM interviews; Acceptability by proportion of unanswered items and participants who answered all items; Reliability through the Cronbach's alpha coefficient and Validity through the convergent construct validity between the TSQM and the adherence measures. Results: TSQM was easily applied. Ceiling effect was found in the side effects domain and floor effect in the side effects and global satisfaction domains. Evidence of reliability was close to satisfied in all domains. The convergent construct validity was partially supported. Conclusions: the Brazilian TSQM presents evidence of acceptability and practicability, although its validity was weakly supported and adequate internal consistency was observed for one domain.